The New-Look Inclination among University Female Students in Hebron Province - Jondi, Nabil Jebreen; Sweeti , Abeer Hasan; Sarahneh , Sereen Salem (Dirasat: Human and Social Sciences, 2024)
Objectives: This study investigated the inclination of female students towards new appearances at Al-Khalil University and Palestine Polytechnic University. It also examined whether there were differences in this inclination based on specific independent variables. Methods: The study involved a sample of 300 female students from both universities in Al-Khalil. A scale was developed to measure their level of interest in new appearances, and criteria were established to categorize the degrees of inclination. Differences in mean scores were analyzed according to university, academic year, and economic level. Results: The findings revealed that female students displayed a moderate inclination towards new appearances. Notably, there were differences favoring Polytechnic University in terms of this inclination. Additionally, the economic status of the students' families played a role, with those from higher income backgrounds showing a greater inclination. Moreover, there were variations related to the students' academic year, favoring second, third, and fourth-year students. Conclusion: The study concluded that the inclination towards new appearances among female university students was linked to economic factors and academic level. To support these students, it is recommended to focus on boosting their self-confidence and considering their preferences within the context of societal norms and prevailing culture.